'A flicker of the divine progress?': stage-managing narratives of Empire in Jan Morris's Pax Britannica trilogy. Issue 4 (3rd April 2023) - Pryor, Judith
ABSTRACT : When Jan Morris died in 2020, people from around the world praised her elegant and eloquent writing, and her extraordinary life. Her many achievements included the publication between 1966 and 1978 of the 'intellectual and artistic high-point of [her] career': the Pax Britannica trilogy charting the zenith and decline of the British Empire. The popular trilogy, which remains in print, played a key role in establishing the late twentieth-century cultural narrative that the British Empire was 'a force for good' in the world. Calling into question the boundary between history, fiction and memory, Morris draws heavily on theatrical techniques to both construct a narrative of Empire, one which is dominated by the adventures of individual imperialists, and draw attention to its fabrication. Attending closely to its mode of address, I argue that Morris's trilogy, while equivocal and, in places, critical, ultimately offers a reassuring narrative of Empire. At a time of debate about these histories, I argue that the memorialising of Morris in the wake of her death represents one example of a continuing refusal to face the ongoing consequences of Empire.